Hereditary characteristics of the S339L mutation in a patient with maple syrup urine disease in Vietnam - Huong, Nguyen Thi Thu; Dung, Vu Chi; Ngan, Nguyen Thi Thanh; Thoa, Nguyen Kim; Hoang, Nguyen Huy (Academia Journal of Biology, 2020)
Maple syrup urine disease (MSUD) is an autosomal recessive inherited metabolic disorder caused by malfunction of the branched-chain α-ketoacid dehydrogenase complex (BCKDH). This enzyme complex participates in the catalyzing metabolisms of the branched-chain α-ketoacids, the second step of the degradation of branched-chain amino acids. Impaired activities of the BCKAD complex lead to an increase of the levels of branched- chain amino acid such as leucine, valine, and isoleucine in the blood. In children with maple syrup urine disease, catalysis of the metabolisms of some amino acids failed to be implemented, leading to an accumulation of the amino acids which has been shown as one of the causes of neurological complications, intellectual disabilities, and nervous paralysis or even death. Pathogenic mutations normally occur in BCKDHA, BCKDHB, DBT and DLD genes which encode the E1α, E1β, and E2 subunits of the BCKDH complex. In the present study, a homozygous mutation in the BCKDHB gene (c. 1016C>T) in a pediatric patient with MSUD diagnosed at The National Hospital of Pediatrics was identified using whole exome and Sanger sequencing methods. As a result, the inheritance of the homozygous mutation related to MSUD in BCKDHB gene within the pedigree of the patient’s family was determined. The results indicated that the mutation in the BCKDHB gene was inherited from both of the patient’s parents. In addition, this finding provides an important scientific basis to researches on MSUD in the Vietnamese population.